Stimulating small-scale farmer innovation and adaptation with Participatory Integrated Climate Services for Agriculture (PICSA): Lessons from successful implementation in Africa, Latin America, the Caribbean and South Asia - Graham Clarkson; Peter Dorward; Sam Poskitt; Roger D. Stern; Dominic Nyirongo; Katiuscia Fara; John Mwangi Gathenya; Caroline G. Staub; Adrian Trotman; Gloriose Nsengiyumva; Francis Torgbor; Diana Giraldo (Climate Services, 2022)
How to cope with climate variability and adapt to climate change are key challenges for smallholder farmers globally. In low-income countries, farmers have typically received little, if any locally relevant weather or climate information. Although climate services have contributed to increased availability and accessibility of climate information, this has rarely achieved the desired impacts for farmers’ decision-making, adaptation and resilience to climate variability and change. This has been attributed to a lack of engagement with intended users of climate information and a top-down approach to development and delivery of climate services that fails to adequately consider and account for farmers’ context-specific requirements. Participatory Integrated Climate Services for Agriculture (PICSA) is an approach that was developed to support and empower farmers in their decision-making processes. More than 200,000 farmers have been trained in 23 countries and this paper presents evidence from evaluations in 7 countries including that most (87%; n = 4,299) have made beneficial changes in their crops, livestock and/or livelihood enterprises. The approach has strengthened key institutions that support farmers through deliberative scoping, tailoring, and capacity-building activities with extension and meteorological services. It has been well received by those that use it and is being integrated into policy and training curricula. Key reasons for the success of the approach include the importance of supporting farmers as decision makers and empowering them to relate relatively complex weather and climate information to their own contexts. Key considerations for the future include ensuring sustainability and further scaling as well as maintaining quality.